Encouraging Compliance and Integrity: Building a Civil Servant Discipline System in terms of the Legal System Aspect - Irma Purwaningsih; Nanik Prasetyoningsih (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Civil Servant (PNS) discipline is a fundamental pillar in creating a state apparatus with integrity and high performance. This article discusses the urgency of building an effective civil servant discipline system based on statutory Law to encourage compliance and integrity. This research uses normative juridical methods by examining statutory regulations related to civil servant discipline, such as the ASN Law and PP 94/2021. The research results show that the current civil servant discipline system still has several areas for improvement, such as a need for firmness in enforcing sanctions and inadequate coaching mechanisms. To build an effective civil servant discipline system, several strategic steps need to be taken, including Strengthening regulations related to civil servant discipline by evaluating and revising existing regulations, Increasing the effectiveness of enforcing disciplinary sanctions by prioritizing the principles of justice and proportionality, Strengthening the role of the Government's internal oversight apparatus in supervising and following up on civil servant disciplinary violations, building a culture of discipline and integrity within government agencies through ongoing education and training. Effective and consistent enforcement of civil servant discipline will encourage the creation of a state apparatus that is professional, has integrity, and has high performance so that it can ultimately support the achievement of national development goals.